Exodus zarobkowy z województwa opolskiego i jego determinanty - Jończy, Romuald (Economic Emigration form the Opolskie Voivodship and Its Determinants, 2007)
The article describes and analyzes determinants of work emigration of inhabitants of the Opole region with a double nationality (Polish and German). As a consequence of the access to the labour market in Western Europe, more than half of the working population works outside Poland. In case of young people we can speak of an exodus, as 84% of the age group 18-25 years works abroad. The basic determinant of emigration for work is not the lack of jobs in the place of living, but the pay-off of work abroad, which is 4 to 7 times higher than in Poland. The article presents research on the demands of emigrants regarding work in Poland and expectations concerning policy of the state and labour market institutions. The analysis of economic factors (prices, wages, and exchange rates) and demographic factors (number of entrants to the labour market) shows that emigration for work may increase during the following years. Much of this emigration may become permanent.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (14); 2007; nr 1164, s. 221-231